2011
DOI: 10.1039/c0cc03166f
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant mediated oxygen reuptake in water for green aerobic oxidation: mass-spectrometric determination of discrete intermediates to correlate oxygen uptake with oxidation efficiency

Abstract: A novel strategy of catalytic green aerobic oxidation by surfactant-mediated oxygen reuptake in water offers a new dimension to the applications of surfactants to look beyond as solubility aids and a conceptual advancement in understanding the role of surfactants in aquatic organic reactions through mass spectrometry guided identification of discrete intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…The applicability of the direct hydroxylation towards various substituted 2-arylbenzothiazoles (Table 1), 9 another bio relevant and sterically hindered DG, demonstrated the versatility with respect to the DG. 10 The presence of Cl, Br, CF 3 , and NO 2 in the 2-aryl moiety appears to be beneficial as such substrates afforded the corresponding hydroxyarenes in better yields compared to that of the unsubstituted analogue 1a/3a.…”
mentioning
confidence: 98%
“…The applicability of the direct hydroxylation towards various substituted 2-arylbenzothiazoles (Table 1), 9 another bio relevant and sterically hindered DG, demonstrated the versatility with respect to the DG. 10 The presence of Cl, Br, CF 3 , and NO 2 in the 2-aryl moiety appears to be beneficial as such substrates afforded the corresponding hydroxyarenes in better yields compared to that of the unsubstituted analogue 1a/3a.…”
mentioning
confidence: 98%
“…These results indicated that the amine component could selectively couple with carbonyl sites of 1 a. Then, when 1H-benzo[d] [1,3]oxazine-2,4-dione (9), which may be generated in situ in the aerobic copper catalysis, was subjected to the present systems, no desired benzothiazole product was formed (Scheme 4, d). Finally, the addition of radical scavenger such as TEMPO and BHT into the systems proved to be no obvious prohibiting effect on the yield (Scheme 4, e), which revealed that the copper-catalyzed aerobic reactions may not proceed through a radical pathway.…”
mentioning
confidence: 72%
“…could also be employed. [9] Despite of the practical effectiveness, those methods suffer from limitations with respect to strong acidic conditions, high reaction temperature, and excessive amounts of oxidant required. More importantly, some synthetically and pharmaceutically useful functionalities such as amino could not be tolerated in these harsh systems.…”
mentioning
confidence: 99%
“…Several examples have been reported in the synthesis of benzo-fused azole compounds under aerobic oxidation conditions [16][17][18][19][20]. With the requirement of sustainable chemistry, some green approaches for the preparation of 2-arylbenzothiazoles via aerobic condensation reaction have also been reported, such as ''on water'' synthesis [21], catalyst-free synthesis [22], photocatalytic synthesis [23].…”
Section: Introductionmentioning
confidence: 99%